Effect of Traditional Process Methods on the Physicochemical and Functional Properties of a Traditional Food Salt (Nikkih) Obtained from Waste Biomass Peels of Musa paradisiaca and Musa acuminate - Pride Ndasi Ngwasiri; Vivian Akah Adanmengwi; Wilson Agwanande Ambindei; Noumo Thierry Ngangmou; Dobgima John Fonmboh; Ngwa Martine Ngwabie; Martin Benoit Ngassoum; Ejoh Richard Aba (International Journal of Chemical Engineering)
In Cameroon, agrofood waste biomass such as peels of Musa paradisiaca and Musa acuminate is being valorized using various traditional processing methods to produce a traditional functional food salt, potash, locally called nikkih. Nikkih has been reported to have varying physicochemical and functional properties, which negatively affect the quality and stability of food prepared using it. This work aims at evaluating the effect of traditional process methods on the physicochemical and functional properties of nikkih produced from these peels in view of the optimization of the process. The peels were preprocessed using two methods: boiling at 90oC before drying and direct drying of raw samples. All samples were dried and combusted to ash at varying temperatures of 250oC, 300o C, and 350oC and times of 30 min, 60 min, and 90 min. The ash obtained was dissolved in varied volumes of water, filtered to obtain the nikkih. Yellow achu soup was prepared through the dry gum method using water and read palm oil, with nikkih as emulsifier. The physicochemical and functional properties of nikkih on yellow achu soup were evaluated using standard methods. The ash yield ranged from 10.62 ± 0.12% to 7.10 ± 0.05%, with the raw samples combusted at 3000C and 2500C having the highest and lowest values respectively. The pH of nikkih ranged from 10.95 ± 0 to 12.01 ± 0.056 while potash content ranged from 32.45 ± 0.905% to 72.29 ± 1.31%, with the highest and lowest values obtained from the raw sample combusted at 2500C and the boiled samples combusted at 3500C respectively. Alkaline content ranged from 61.7 ± 0.141% to 52.8 ± 0.141%, with boiled M. acuminate combusted at 3500C having the highest value and the lowest from raw M. paradisiaca combusted at 2500C. The foaming capacity and foam stability ranged from 6.9 ± 0.01% to 16.07 ± 2.51% and from 3.20 ± 0.07% to 11.205 ± 2.39% for M. acuminate and M. paradisiaca respectively. The emulsification index ranged from 85.62 ± 0.09% to 86.67 ± 1.141% after 24 hrs and from 26.0 ± 0.94% to 27.02 ± 2.390% after 48 hrs, with the highest value from the raw M. acuminate combusted at 350oC and the lowest from that combusted at 3000C. The potash source, pretreatment method, combustion conditions, and dilution factors all had an effect on the physicochemical and functional properties of nikkih.